Vergilendirmenin gelir dağılımına etkileri ve Türkiye’deki durumu - Kürsüz, Tuğba (My University, 2010)
Anahtar Kelimeleri :Vergi Yansıması, Gelir Dağılımı, Kayıtdışı Ekonomi ÖZET VERGİLENDİRMENİN GELİR DAĞILIMINA ETKİLERİ VE TÜRKİYE’DEKİ DURUMU Bu tezin amacı vergilerin gelir dağılımı üzerindeki etkilerini araştırmaktır. Bu doğrultuda öncelikle gelir dağılımı kavramı ve önemi üzerinde durulmuş, gelir dağılımı teorileri ele alınmıştır. Vergilerin yapıları irdelenerek gelir dağılımı üzerindeki etkileri önce genel olarak, son olarak da Türkiye baz alınarak incelenmiştir. Piyasaya devlet müdahalesi olmazsa gelir dağılımı adil olmamaktadır. Devlet gelir dağılımını sağlamak için vergi veya harcama politikasını kullanmaktadır. Vergi yükünün düşük gelirliler lehine olmasıyla, yani düşük gelir grubu üzerinde hafifleştirilerek yüksek gelir grubu üzerinde ise ağırlaştırılarak adil bir gelir dağılımı sağlanabilir. Bir ülkede kayıtdışı ekonomi veya vergi yansıması varsa vergi yükü tam olarak hesaplanamamakta bunun sonucunda da vergilerin gelir dağılımı üzerindeki etkileri tam olarak saptanamamaktadır. Tezimde; yukarıda bahsedilen kavramlar çerçevesinde vergilerin gelir dağılımı üzerindeki etkileri araştırılacak ve Türkiye analizi yapılacaktır. Tax Reflection, Income Distribution, Informal Economy

THE EFFECTS OF TAXATION ON THE INCOME DISTRIBUTION AND THE SITUATION IN TURKEY The aim of this thesis was to investigate the effects of taxes on the income distribution. In this respect the concept and importance of the income distribution primarily focuses on the theories of income distribution are discussed. By examining the structure of the taxes The effects on the income distribution is analyzed first in general then on the basis of Turkey. The income distribution is not fair without government intervention on the market. The government uses income tax or spending policy to ensure the distribution of income. Setting up low tax for low income community in favour and increased tax for high income community makes more justiced income range. If the reflection of a country, the informal economy or the tax calculated in exactly the tax burden as a result, the effects of taxes on the income distribution is identified exactly. If there is informal economy or tax reflection in a country, taxation charge can not be calculated exactly. As a result the effects of taxes on the income distribution can not be determinated. In my thesis, the effects of the taxes on income distribution were investigated and the situation of Turkey was analyzed within the framework of the above-mentioned concepts.
Keywords: Gelir Dağılımı; Gelir Vergisi_Türkiye; Vergilendirme